Introduction to topic maps model (ISO/IEC13250:2003) - Colmenero Ruiz, Maria Jesús (2005)
The librarian capability of guiding the information sources system learning It was made a revision of standard ISO/IEC 13250:2003 Topic Maps, standing out its possibilities in the documentary scope. After describes its historical evolution and the present situation the concepts that compose this model, the three basic elements (topic, association, and occurrence) are developed and two more (scope and public subject), analyzing its possibilities for the organization of the knowledge, like semantic structure of browsingn and for the interoperability. The most interesting elements of specification XTM 1,0 are analyzed and, finally, some of the surroundings are detailed in which it is being applied.